Contract compliance under biased expectations: Evidence from an experiment in Ghana - Sabine Fischer; Kerstin Grosch (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
Contract compliance is key for economic growth. However, determinants affecting contract breach are not yet well understood. In this paper, we focus on contract situations with a potential hold-up problem, such as contract farming agreements which are prevalent in many developing countries. We examine if agents' payoff expectations serve as a reference point affecting (non-)compliant behavior by inducing a subjective loss when the agent compares the realized payoff and the expected payoff from the contract. Results from our lab experiment in Ghana indicate that overconfident agents, i.e., agents with relatively high payoff expectations, breach more often than underconfident agents, i.e., agents with relatively low payoff expectations. Moreover, more pronounced individual loss aversion amplifies the effect of subjective losses on contract breach. In a treatment, we manipulate agent's overestimation exogenously and use it as an instrument to demonstrate that the reported effects are causal.
Keywords: C91; D03; D81; D84; J41; O12; 330; contract compliance; overconfidence; reference-dependent preferences